Temporal dynamics of chicken host’s molecular response against Fowl adenovirus serotype 8b infection via RNA-sequencing - Azli, Bahiyah; Salim, Nur Farhana; Hair-Bejo, Mohd; Omar, Abdul Rahman; Mohamed Sohaimi, Norfitriah; Clifford, Ugwu Chidozie; Abdul Hamid, Nor Asilah Wati; Mat Isa, Nurulfiza (BioMed Central, 2025)
Background: Fowl adenovirus serotype 8b (FAdV-8b) is the etiological agent of inclusion body hepatitis’ outbreaks in chicken farms worldwide and a threat to the poultry industry. The isolation and identification of isolates of this pathogen are abundant, yet the pathogenesis and subsequent molecular mechanism are significantly understudied. Hence, this study aims to identify the differential gene expression profile of specific pathogen-free chicken livers infected with FAdV-8b strain UPMT1901 isolate. Results: The harvested chicken livers were subjected to biological pooling and transcriptomic profiling via RNA-sequencing, according to the days of post-infections (dpi). A total of 21,662 genes were identified in both control and infected groups, enriched in various biological processes and pathways, displaying patterns of disease progressions. The transcriptome analysis results revealed a three-fold reduced pattern of gene regulation with 9146, 7335, and 3800 significant differential expressed genes (DEGs) at 2-, 5-, and 7-dpi (dpi), respectively. Conclusion: These findings elucidate insights on the holistic disease progression of FAdV-8b in liver, from viral incubation and replication at 0–2-dpi, major metabolite hijacking at 3–5-dpi, followed by constant regulation of immune response at 6- and 7-dpi. Based on intensive literature review conducted prior to this study, this study is considered as the first study of the serotype 8b infection pathogenesis at the target organ, providing a better understanding and wide basis of pathogen-host interaction in FAdV-8b in chickens and its progression.